Electroacupuncture Pretreatment Attenuates Cerebral Ischemia-Reperfusion Injury in Rats Through Transient Receptor Potential Vanilloid 1-Mediated Anti-apoptosis via Inhibiting NF-κB Signaling Pathway. (1st February 2022) - Long, Man; Wang, Zhigang; Shao, Luyao; Bi, Jing; Chen, Zebin; Yin, Nina
Graphical abstract: Highlights: EA pretreatment at GV20, bilateral BL23 and SP6 acupoints exerts neuroprotection against CIRI. TRPV1-mediated anti-apoptosis participates in the neuroprotective effects of EA pretreatment. Inhibiting NF-kB signaling is associated with regulation of TRPV1-mediated anti-apoptosis. Abstract: Our previous study showed that electroacupuncture (EA) pretreatment elicited protective effect on cerebral ischemia–reperfusion injury (CIRI) in rats, at least partly, which was associated with transient receptor potential vanilloid 1 (TRPV1)-regulated anti-oxidant stress and anti-inflammation. In this study, we further investigated the possible contribution of TRPV1-mediated anti-apoptosis in EA pretreatment-evoked neuroprotection in CIRI. After EA pretreatment at Baihui (GV20), bilateral Shenshu (BL23) and Sanyinjiao (SP6) acupoints, transient focal cerebral ischemia was induced by middle cerebral artery occlusion (MCAO) for 2 h followed by reperfusion for 6 h in rats. Then, infarct volume, nerve cell injury, neuronal apoptosis, NF-κB signaling activation, and expression of TRPV1 were evaluated by TTC staining, Hematoxylin–Eosin staining, transmission electron microscopy, immunochemistry, immunofluorescence, and Western blot, respectively. The presented data showed that EA pretreatment significantly reduced infarct volume, relieved nerve cell injury, decreased the expression of pro-apoptotic proteins Bax and cleaved caspase-3, increased the level of anti-apoptotic protein Bcl-2, inhibited NF-κB (p65) transcriptional activity, and curbed TRPV1 expression in MCAO rats. By contrast, enhancement of TRPV1 expression accompanying capsaicin application, the specific TRPV1 agonists, markedly accelerated nerve cell damage, aggravated neuronal apoptosis, prompted nuclear translocation of NF-κB (p65), resulting in the reversion of EA pretreatment-evoked neuroprotective effect in MCAO rats. Thus, we conclude that EA pretreatment-induced downregulation of neuronal TRPV1 expression plays an anti-apoptosis role through inhibiting NF-κB signaling pathway, thereby protecting MCAO rats from cerebral ischemia–reperfusion injury.